Aspek Bersyukur pada Puisi “Bersyukur Kau Tidak Lahir Dari Hujan” Karya Ahmad Nurullah dan Cerpen “Bersyukur” Karya Sudut Kamar - Iswantari, Sandika; Maharani, Eviana; Wulandari, Yosi (Jurnal Pena Indonesia, 2024)
This research aims to describe the inner structure in the poem “Bersyukur Kau tidak Lahir dari Hujan” by Ahmad Nurullah and the intrinsic structure in the short story "Bersyukur" by Sudut Kamar. This research method is a descriptive method related to the subject matter that will be researched and obtained from research data. The approach used is an intertextual approach. The technique used in data collection is literature study and data analysis techniques using content analysis techniques. The results of research show that the similarities between this short story and poetry are in the theme, namely the theme of gratitude and the same mandate to let each other go for something that we do not yet have, then God will replace it with something unexpected. The difference between poetry and short stories lies in the feeling and setting.